If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.6(x + -18) + 1.3(x + 3) = x + 34 Reorder the terms: -1.6(-18 + x) + 1.3(x + 3) = x + 34 (-18 * -1.6 + x * -1.6) + 1.3(x + 3) = x + 34 (28.8 + -1.6x) + 1.3(x + 3) = x + 34 Reorder the terms: 28.8 + -1.6x + 1.3(3 + x) = x + 34 28.8 + -1.6x + (3 * 1.3 + x * 1.3) = x + 34 28.8 + -1.6x + (3.9 + 1.3x) = x + 34 Reorder the terms: 28.8 + 3.9 + -1.6x + 1.3x = x + 34 Combine like terms: 28.8 + 3.9 = 32.7 32.7 + -1.6x + 1.3x = x + 34 Combine like terms: -1.6x + 1.3x = -0.3x 32.7 + -0.3x = x + 34 Reorder the terms: 32.7 + -0.3x = 34 + x Solving 32.7 + -0.3x = 34 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 32.7 + -0.3x + -1x = 34 + x + -1x Combine like terms: -0.3x + -1x = -1.3x 32.7 + -1.3x = 34 + x + -1x Combine like terms: x + -1x = 0 32.7 + -1.3x = 34 + 0 32.7 + -1.3x = 34 Add '-32.7' to each side of the equation. 32.7 + -32.7 + -1.3x = 34 + -32.7 Combine like terms: 32.7 + -32.7 = 0.0 0.0 + -1.3x = 34 + -32.7 -1.3x = 34 + -32.7 Combine like terms: 34 + -32.7 = 1.3 -1.3x = 1.3 Divide each side by '-1.3'. x = -1 Simplifying x = -1
| -x^2+12x+28=0 | | -1.6(x-18)+0.5(x+3)=x-8 | | 11x+8=4x-27 | | x+3/2*8=x/8 | | 4+3a=4(a+2) | | 5b^2-22b+8=0 | | 4z^2+12z-az-3a= | | 6+4n=2 | | T^2+23t+90=0 | | 2b^2+5b-12=0 | | 4=x+14 | | 12b^2-7b+1=0 | | 4=x+10 | | x-18=3x | | 4(x+2y)= | | n-8(1+n)=-4n-32 | | -3y+12=-2(3y+6) | | 4x+3=c | | 5((-8-3y)-2)-2y=-1 | | n-8(1+n)=-4-32 | | y=6x-x^2-8 | | 3b^2-16b+5=0 | | 2x^3+14x^2+24x= | | 2b^2-b-10=0 | | -(y+12)=4 | | 21-5=4 | | 0.8x+4=12 | | -9(t-4)-(t+5)=3 | | 3b^2-13b+4=0 | | 3x^6y^4+27x^4y^3+15xy= | | -9+3k=6(k+2) | | 8+6y=0 |